(untitled) (Bangladesh Critical Care Journal, 2019)
We present a case of a 45 years old male, diabetic and hypertensive who was admited into hospital with a history ofrestlessness, blurring of vision and breathlessness for one day. Inspite of conservative treatment for 10 hours, hisgeneral condition gradually detoriated and he was shifted to ICU. He was kept on mechanical ventilator. Hislaboratory results showed severe high anion gap metabolic acidosis not corrected by sodibicarb and adequate fluidresuscitation. MRI of brain showed bilateral putamenal lesion suspecting methanol intoxication. His acidosis persistedand after giving 3 sessions of Sustained Low Efficiency Dialysis (SLED), metabolic acidosis was corrected withnormalization of renal function. After six months in a follow-up, patient complained of total blindness and fundalphotography showed bilateral optic atrophy. Bangladesh Crit Care J September 2019; 7(2): 111-112